Crossing lines: Structural advantages of inter-racial criminal street gang violence - Bichler, Gisela (Trends in organized crime, 2024)
Since gang violence typically occurs within racial and ethnic communities, gangs observed to launch counter-normative, inter-racial attacks draw attention to the variable social processes that may underpin conflict relations. Controlling for other factors previously found to influence the structure of gang-on-gang conflict, this study investigated whether gangs launching inter-racial attacks were placing themselves in a strategic position that may offer networked advantages for criminal enterprise. Examining the conflict patterns of 136 criminal street gangs operating in the City of Los Angeles we observed structural characteristics akin to what is observed among successful organizations interlinked by competitive business relations. MR-QAP nodal regression models suggest that gang violence reflects structurally efficient attack patterns. Sensitivity analysis confirmed the robustness of our main results. We conclude that inter-racial patterns of street gang violence may reflect a subset of violence associated with competitive processes that advance criminal enterprise.